PEMBERDAYAAN SISWA SMA PLUS AL-MANSHURIYAH SUKABUMI MELALUI PELATIHAN BUSINESS MODEL CANVAS UNTUK MENUMBUHKAN MINAT BERWIRAUSAHA - Ginanjar, Noornissa Sarah; Setiatin, Tuti; Sobar, Agus (HARUPAT: Jurnal Pengabdian Masyarakat Multidisiplin, 2025)
Empowering the younger generation through entrepreneurship education is a strategic effort to foster independence and enhance the competitiveness of human resources. However, entrepreneurial interest among senior high school students remains relatively low due to limited understanding of business concepts and a lack of practical experience. This community service activity aimed to empower students of SMA Plus Al-Manshuriyah through Business Model Canvas (BMC) training as an effort to stimulate entrepreneurial interest. The activity was conducted in one day, on August 25, 2025, using participatory and applicative methods, which included stages of preparation, training, practice and mentoring, and evaluation. The results indicated an improvement in students’ understanding of entrepreneurship concepts and the nine elements of the Business Model Canvas. In addition, students demonstrated increased creativity, active participation, self-confidence, and interest in designing and developing business ideas independently. Therefore, Business Model Canvas training proved to be effective as a means of strengthening entrepreneurship education and empowering senior high school students.